Efficacy of frozen autograft treated with liquid nitrogen in limb-sparing surgery in feline scapular osteosarcoma: A case report - AKASAKA, Minori (J Vet Med Sci, 2019)
In recent years, a novel technique of limb preservation has been used in human medicine that involves frozen autograft treated with liquid nitrogen. In this case, frozen autograft treatment along with shoulder joint reconstruction was performed in an 11-year-old cat with osteosarcoma of the distal scapula. Surgical site infection, shoulder dislocation, local recurrence, and pulmonary metastases were not reported for 24 months after surgery. Moreover, the patient was able to bear weight on the operated limb after 2 months of surgery, and excellent limb function without lameness was demonstrated after 15 months. The frozen autograft technique is advantageous because it is inexpensive, simple, and retains its initial strength after treatment, and could be a novel treatment in feline osteosarcoma.